Children’s School Readiness: Teachers’ and Parents’ Perceptions - Anayanti Rahmawati; Mareyke Maritje Wagey Tairas; Nur Ainy Fardana Nawangsari (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2018)
ABSTRACT The initial period of adjustment is something to be concerned about since it serves as a period, allowing to lay foundation for education which will contribute to children’s future academic life. It is not an easy period for children due to several school demands and expectations which should be fulfilled by children. To deal with this, children’s school readiness to attend their primary school is required. This qualitative research seeks to find out factors influencing children’s readiness to attend a primary school. The subjects of the research involved teachers and parents of children who planned to apply for admission into primary schools. The research results indicate that both teachers and parents of children shared the same perceptions regarding factors influencing the school readiness: cognitive and noncognitive factors. The former which involve reading, writing, and calculating skills are regarded significant since such skills are used as admission prerequisites for primary level in certain schools. Similarly, the latter are supposed to be important since they support children to successfully adjust to their primary school. Keywords: school readiness; primary school; children